Varying tube voltage and pitch effects on dose and image quality using single-energy CT / Noor Shafini Mohamad, Nur Alyaa Adnan - Mohamad, Noor Shafini; Adnan, Nur Alyaa (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Second generation of Computed Tomography (CT) with tin filtration is one of dose reduction strategies in advanced CT system. Taken advantage of high pitch mode as another parameter to reduce dose, will results in an increase spatial resolution and reduce acquisition time. In the present study, we have examined the effect of varying tube voltage and pitch on dose and image quality using Single-Energy CT with tin filter. a cow liver was used as an ex vivo phantom. The tube voltages were set at 80,100,120 and 140 kV whilst pitch factors 0.5, 0.6, 0.8, 1.0 and 1.2. Commonly, 120 kV and 1.0 pitch are used in standard protocol in CT, therefore, they are used as a reference for the study. The mean CTDIvol, Hounsfield Unit (HU) Number and Signal-to-Noise Ratio (SNR) at different level of kV and pitch were measured over a homogenous area of the liver phantom and the results were compared among the groups. In conclusion, performance of CT using 120 kVp and 1.2 pitch achieved reduction of radiation dose by 16% without impairing image quality with relatively higher SNR.